Mixed convection boundary layer flow near the lower stagnation point of an isothermal solid sphere in a nanofluid - Leony Tham; Roslinda Nazar; Ioan Pop (2013)
In this paper, the problem of steady mixed convection boundary layer flow in a nanofluid near the lower stagnation point of a solid sphere in a stream flowing vertically upwards has been studied for both cases of heated and cooled spheres. The resulting system of nonlinear partial differential equations is solved numerically using an efficient implicit finite-difference scheme known as the Keller-Box method. Three different types of nanoparticles considered are copper Cu, alumina and titania by using water-based fluid with Prandtl number at 6.2. Numerical solutions are obtained for the velocity and temperature profiles with various values of the nanoparticle volume fraction j and the mixed convection parameter l.